(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
In psycho-therapy, methods of therapy have been more richly developed and better understood than the subject matter – the psyche – they endeavour to treat. This paper clarifies the ontological nature of psyche by considering its core etymological meaning, Heidegger’s understanding of self as Dasein and the Buddhist notion of self as non-self.